Lights, Camera, Amalee - Williams, Dar (SCHOLASTIC INC., 2006)
"A poignant, funny debut... readers will be charmed by William's eccentric, lovable characters and her sharp observations about the world of both middle-schoolers and adults" "An uplifting story that will grab young readers"